Long term follow‐up after ventricular tachycardia ablation in patients with congenital heart disease. (11th June 2019) - Yang, Jiandu; Brunnquell, Michael; Liang, Jackson J.; Callans, David J.; Garcia, Fermin C.; Lin, David; Frankel, David S.; Kay, Joseph; Marchlinski, Francis E.; Tzou, Wendy; Sauer, William H.; Liu, Bolun; et al.
Abstract: Background: Ventricular tachycardia (VT) is frequently encountered in patients with repaired and unrepaired congenital heart disease (CHD), causing significant morbidity and sudden cardiac death. Data regarding underlying VT mechanisms and optimal ablation strategies in these patients remain limited. Objective: To describe the electrophysiologic mechanisms, ablation strategies, and long‐term outcomes in patients with CHD undergoing VT ablation. Methods: Forty‐eight patients (mean age 41.3 ± 13.3 years, 77.1% male) with CHD underwent a total of 57 VT ablation procedures at two centers from 2000 to 2017. Electrophysiologic and follow‐up data were analyzed. Results: Of the 77 different VTs induced at initial or repeat ablation, the underlying mechanism in 62 (81.0%) was due to scar‐related re‐entry; the remaining included four His‐Purkinje system–related macrore‐entry VTs and focal VTs mainly originating from the outflow tract region (8 of 11, 72.7%). VT‐free survival after a single procedure was 72.9% (35 of 48) at a median follow‐up of 53 months. VT‐free survival after multiple procedures was 85.4% (41 of 48) at a median follow‐up of 52 months. There were no major complications. Three patients died during the follow‐up period from nonarrhythmic causes, including heart failure and cardiac surgery complication. Conclusion: While scar‐related re‐entry is the most common VT mechanism in patients with CHD, importantly, nonscar‐related VT may also be present. In experienced tertiary care centers, ablation of both scar‐related and nonscar‐related VT in patients with CHD is safe, feasible, and effective over long‐term follow‐up.